Can Coenzyme Q10 Supplementation Reduce Cardiovascular Disease Risk Factors? A Protocol for a GRADE‐Assessed Systematic Review and Dose‐Response Meta‐Analysis of Randomized Controlled Trials - Ali Jafari (Health Science Reports)
ABSTRACT Background and Aims Cardiovascular diseases (CVDs), encompassing a variety of conditions affecting the heart and blood vessels, remain a significant global public health challenge. Among various therapeutic options, Coenzyme Q10 (CoQ10) has garnered attention due to its potential benefits for cardiovascular health. CoQ10 is a naturally occurring antioxidant that plays a crucial role in cellular energy production and has long been used therapeutically. This study aims to summarize and systematically analyze the scientific literature on glycemic profile, lipid profile, anthropometric measures, blood pressure, inflammatory factors, liver function tests, oxidative stress parameters and adipokines associated with CoQ10 supplementation to provide a basis for clinical treatment. Methods A systematic electronic search will be conducted to identify articles published from inception to July 2024 across databases including PubMed, Scopus, Web of Science, CENTRAL, and EMBASE. The search will focus on randomized controlled trials (RCTs) involving both healthy and unhealthy participants. Two independent reviewers will evaluate articles, extract data, and assess study quality using the Cochrane risk of bias tool. Discrepancies will be resolved through consultation with a third reviewer. If a sufficient number of eligible studies are identified, a meta‐analysis will be performed on the selected outcomes. Results The results will provide a comprehensive synthesis of the effects of CoQ10 supplementation on cardiovascular disease risk factors, including glycemic profile, lipid profile, anthropometric measures, blood pressure, inflammatory factors, liver function tests, oxidative stress parameters, and adipokines. Conclusion This protocol outlines a comprehensive approach to systematically review and perform a dose–response meta‐analysis on the effects of CoQ10 supplementation on CVD risk factors. The study will employ rigorous methodologies, including independent evaluation and GRADE assessment, to ensure high‐quality evidence synthesis from RCTs.